Uma avaliação da implementação do Programa Proinfância em Erechim: a política dos espaços escolares - Klosinski, Daniele Vanessa (2016)
When we evaluating a governmental and social program whose main purpose is to create school spaces for Early Childhood Education, brings us a great responsibility to these supply policy for the first childhood. The theme of this study is the Educational Public Policy for the First Childhood Education and the School Space, with a focus on the “Proinfância” Program, a government program that aims to build school units of First Childhood Education through a standard project, as well as available equipment and furniture for these units. The research was developed through studies into the structure of these spaces, from a historical understanding, social and childhood policy, the different contexts in which they had the care of small children over the years, as well as social policies and what determines the law on the financing of first childhood education. The study discusses the descriptive memorials of each project provided by the program, as well as Infrastructure Basic Parameters for First Childhood Education schools. Research in essence is through an incursion in first Childhood Education, in Erechim/RS, where the present data on Public Schools, the policy is Philanthropy, Community and buying private schools vacancies, the use and disposition of physical spaces that makes up this policy and the “Proinfância” Program has as municipal responsibility. The labor summit starts from the chapter where exactly develops the evaluation with qualitative data are established parameters from the very well-founded studies conducted by Kowaltowski (2011), from which they organize comparative tables between schools, which treat descriptive memorials and prospects indicated by the author. In the conclusion, we address the issues that were presented in the evaluation tables with notes and essential topics suggestions for the reformulation of school physical spaces of the program, based on reflections and contextualized analysis and taking into account the child lying inserted in this space. Finally, it is stated with all certainty that this program is the first step of building school spaces. Policy for the first Childhood Education, still needs to advance much and this research comes as one of the supports to rethink and restructure the program, aiming to developers, policy makers, and social programs notes that qualify and advance the process of public education in Brazil.